Family physicians' intention to support women in making informed decisions about breast cancer screening with mammography: a cross-sectional survey. (December 2015) - Kiyang, Lawrence-Ndoh; Labrecque, Michel; Doualla-Bell, Florence; Turcotte, Stéphane; Farley, Céline; Cionti Bas, Myrtha; Blais, Johanne; Légaré, France
Abstract Background The net benefits of routine breast cancer screening with mammography have been questioned, and there is evidence to indicate that supporting women to make an informed decision about breast cancer screening with mammography is preferable. The aims of this study were to assess the intention of family physicians to provide women with this support and the determinants of this intention, and to identify factors that might influence family physicians adopting this behavior. Methods Family physicians from the province of Quebec, Canada, attending a 45-min lecture on informed decision making and cancer screening were asked to complete a questionnaire after the lecture regarding their intention to adopt the behavior. The questions, based on the Theory of Planned Behavior, measured physicians' intention and its determinants (attitude, perceived behavioral control, and socio-professional norm) regarding supporting women to make informed decisions about breast cancer screening with mammography. Open-ended questions were also used to explore complementary factors influencing their intention. Results Out of 800 questionnaires distributed, 301 (38 %) were returned and 288 were included in data analysis. The mean ± standard deviation and median score for intention were respectively 1.9 ± 1.2 and 2.0 on a 6-point Likert scale (−3 to +3). Perceived behavioral control was the variable most strongly associated with intention (high versus low score, odds ratio = 15.7, 95 % CI 6.7–36.6), followed by attitude (high versus low score, odds ratio = 7.5, 95 % CI 3.3–16.8), then social norm (high versus low score, odds ratio = 5.8, 95 % CI 2.6–12.9). The most-reported barrier to adopting the behavior was time constraints (41 %) while the most-reported facilitator was availability of relevant decision support tools (29 %). Conclusions Respondents showed strong intention to support women in informed decision-making about breast cancer screening, the strongest predictor being perceived behavioral control. These results could contribute to training physicians to integrate this behavior into their practices and to designing relevant decision support tools.